2018
DOI: 10.1155/2018/4103232
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Casts for Orthodontic Purpose Using Powder-Free Intraoral Scanners: Accuracy, Execution Time, and Patient Feedback

Abstract: Introduction Intraoral scanners allow direct images of oral situation, with fewer steps than conventional impressions. The purpose of this study was to compare the accuracy of digital impressions, traditional impressions, and digitalization of full-arch gypsum models, to evaluate timing of different methods and finally to study perception of patients about conventional and digital impression techniques. Methods Dental arches of fourteen patients were evaluated by alginate impression, titanium dioxide powder-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 31 publications
1
78
0
12
Order By: Relevance
“…Although not taken into consideration in this study, another variable that could influence the results of time investigation is packaging. In fact, some research took into consideration also packaging time for alginate impressions compared with the time needed to compress and send file to laboratory for digital models, showing a reduction in total time for digital impressions …”
Section: Discussionmentioning
confidence: 99%
“…Although not taken into consideration in this study, another variable that could influence the results of time investigation is packaging. In fact, some research took into consideration also packaging time for alginate impressions compared with the time needed to compress and send file to laboratory for digital models, showing a reduction in total time for digital impressions …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recently introduced intraoral scanners can be integrated with the described system, in order to have a direct three-dimensional (3D) reproduction of dental arches without intermediate passages. These impression systems allow for an easy interaction with CAD/CAM printers and thus a completely digital workflow, with sufficient clinical precision and greater patients' satisfaction if compared with conventional impression methods [29]. Stress-sensing chips may experience degraded performance under high temperature and high stress.…”
Section: Embedding Challengesmentioning
confidence: 99%
“…Recently, zirconia and glass-ceramic have been successfully followed by CAD/CAM technology [41]. Additionally, Alessandretti et al [42] suggested a completely digital workflow, from digital impressions to the final framework, with excellent patient feedback [43] and clinical reliability. Therefore, this technique seems to be particularly indicated for pediatric patients.…”
Section: Discussionmentioning
confidence: 99%